Effects of multidimensional life management on healthy behavior in polycystic ovary syndrome patients: A randomized controlled trial - Guo, Yunmei; Liu, Ying; Yan, Xin; Ding, Rui; Wang, LianHong (Frontiers in Psychology, 2022)
Objective To confirm the effects of a transtheoretical model (TTM) based on multidimensional life management on healthy behavior in patients with polycystic ovary syndrome (PCOS). Methods In total, eighty eligible patients were recruited from March 2021 to June 2021 and randomly assigned to either the intervention (n = 40) or control (n = 40) groups. Outcome measures include health-promoting behavior, self-efficacy, anthropometrics, and the number of unplanned outpatient admissions. Data were collected at baseline, 3, and 6 months after the intervention. The chi-square test, rank-sum test, t-test, and repeated measurement analysis of variance (ANOVA) were used to analyze the data. Results In total, sixty-six participants completed the study: 35 participants in the intervention group and 31 participants in the control group. After 6 months of intervention, the healthy behavior level of patients with PCOS increased from moderate [health-promoting lifestyle profile (HPLP)-II score of 105.37 ± 12.57] to good (156.94 ± 19.36) in the intervention group; and there was no change observed in the control group. In addition, the total self-efficacy score (p < 0.001), PCOS-related unplanned outpatient admissions (p = 0.008), waist circumference (WC) (p = 0.016), and body mass index (BMI) (p = 0.011) were found to have a significant difference in the intervention group at 6 months. Meanwhile, repeated measures analysis of variance showed a significantly greater improvement in health-promoting behavior and self-efficacy over time in the intervention group than in the control group (p < 0.001). Conclusion The transtheoretical model based on multidimensional life management positively affected healthy behavior, self-efficacy, the number of unplanned outpatient admissions, and anthropometrics in patients with PCOS. Clinical Trial Registration www.chictr.org.cn, ChiCTR2000034572.